Nasal vaccination of β7 integrin‐deficient mice retains elevated IgA immunity. Issue 8 (8th July 2020) - Maślanka, Tomasz; Clapp, Beata; Hoffman, Carol; Robison, Amanda; Gregorczyk, Izabela; Pascual, David W
Abstract: Understanding the migration of lymphocytes to nonintestinal mucosal sites is fundamental to developing mucosal vaccination strategies. Studies have shown that nasal and oral immunization with cholera toxin (CT) stimulates, in addition to α4β7 +, the induction of αE (CD103)β7 + B cells. To determine the extent to which αE‐associated β7 contributes to antigen (Ag)‐specific immunoglobulin (Ig)A responses in the upper respiratory tract, nasal CT vaccination was performed in wild‐type (wt) and β7 −/− mice. At 16 days postprimary immunization, upper respiratory tract IgA responses were greater in β7 −/− mice than in wt mice. IgA induction by distal β7 −/− Peyer's patches, mesenteric lymph nodes and small intestinal lamina propria was minimal, in contrast to elevated gut IgA responses in wt mice. By 42 days postprimary immunization, β7 −/− gut IgA responses were restored, and upper respiratory tract Ag‐specific IgA responses were equivalent to those of wt mice. Examination of homing receptor expression and cell‐sorting experiments revealed that β7 −/− mice have increased usage of β1 and αE integrins by upper respiratory tract B cells, suggesting that alternative integrins can facilitate lymphocyte migration to the upper respiratory tract, especially in the absence of β7. Abstract : B‐lymphocyte migration in the upper respiratory tract was found to be enhanced in the absence of β7 integrin. More than half of the antigen‐specific B cells in the head and neck lymph nodes, nasopharyngeal‐associated lymphoid tissue and nasal passages were found to express αE(CD103) integrin. These studies show that B‐lymphocyte migration in the upper respiratory track is less dependent on α4β7, unlike intestinal B cells.